Time from sudden sensory neural hearing loss to treatment as a prognostic factor - Chen, Itay; Eligal, Shalom; Menahem, Ori; Salem, Riki; Sichel, Jean-Yves; Perez, Ronen; Shaul, Chanan (Frontiers in Neurology, 2023)
Introduction The widely accepted treatment for sudden sensorineural hearing loss (SSNHL) is corticosteroid treatment (oral or intratympanic). The main goal of this work is to define the significance of the time between symptom onset and treatment initiation, as well as other prognostic factors, for hearing improvement. Methods This retrospective study included 666 patients treated for SSNHL. Demographic data, audiometry, treatment method, time since symptom onset, and associated symptoms were recorded for each patient. The patients were divided into five groups according to the treatment initiation time—half a week, one week, 2 weeks, 3 weeks, or 4 weeks and over—after symptom onset. The degree of improvement was assessed by comparing the audiometry at the beginning and the end of the treatment. Results The average period of hearing loss from symptom onset to treatment initiation was 10.8 days. Significant differences were found between the groups of half a week, one week, and 2 weeks and the groups of 3 weeks and 4 weeks and over (each separately, p < 0.001). No difference was found between the half-week, one-week, and two-week groups, nor was there a difference between the three-week and four-week-and-over groups. A correlation was found between the treatment initiation time in days and the degree of improvement in hearing for both speech recognition threshold (SRT) and discrimination, R = 0.26 p < 0.001 and R = 0.17 p < 0.001, respectively. No correlation was found for gender, age of the patients, comorbidities, or associated symptoms. Conclusion The threshold for treatment initiation time is up to 2 weeks, after which the amplitude of hearing improvement decreases significantly. The other prognostic factors measured were not found to be statistically significant predictors.